1997
DOI: 10.1124/mol.52.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Gene Expression during Ontogeny in Murine Thymus on Activation of the Aryl Hydrocarbon Receptor by 2,3,7,8-Tetrachlorodibenzo-p-dioxin

Abstract: 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) binds and activates the aryl hydrocarbon receptor (Ah-R), an endogenous transcription factor that is expressed in the thymus. TCDD exposure leads, among other effects, to thymus atrophy and immunosuppression. We previously analyzed the interference of TCDD with differentiation processes in fetal thymus organ cultures and found that in the presence of TCDD, the proliferation rate of immature (CD4- CD8- and CD4- CD8+ HSA+) thymocytes is inhibited, whereas the maturation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 42 publications
2
37
0
Order By: Relevance
“…As shown in Fig. 4B, TCDD increased IL-2 mRNA in total thymocytes, confirming previously published results (15). The overall increase was attributable to the immature CD4 Ϫ CD8 Ϫ cells and future cytotoxic CD4 Ϫ CD8 ϩ cells, both of which responded to TCDD exposure with a strong (ϳ3-and 5-fold) increase of IL-2 mRNA.…”
Section: Il-2 Dre Isupporting
confidence: 78%
See 3 more Smart Citations
“…As shown in Fig. 4B, TCDD increased IL-2 mRNA in total thymocytes, confirming previously published results (15). The overall increase was attributable to the immature CD4 Ϫ CD8 Ϫ cells and future cytotoxic CD4 Ϫ CD8 ϩ cells, both of which responded to TCDD exposure with a strong (ϳ3-and 5-fold) increase of IL-2 mRNA.…”
Section: Il-2 Dre Isupporting
confidence: 78%
“…IL-2 promoter activity is regulated by a number of elements, i.e., Oct-1, NFAT, NF-B, and AP-1, which cooperate and thus confer the lineage specificity and external regulation of IL-2. Others and we had shown that IL-2 expression could be induced by TCDD, i.e., the AHR (15,31,32). Extending these findings, our analysis of IL-2 induction in subpopulations of thymocytes showed that TCDD can induce IL-2 mRNA in…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(13). Additionally, in vitro studies using fetal mouse thymus cultures have suggested that TCDD exposure can disrupt the pattern of thymocyte maturation (14).…”
Section: The Immune Systemmentioning
confidence: 99%